2020
DOI: 10.21203/rs.3.rs-68375/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficiency of damage control orthopaedics strategy in the management of military ballistic limb trauma

Abstract: Background: In conflict areas, orthopaedic surgeon adopted this concept of damage control orthopaedic (DCO) to face limb fracture due to ballistic trauma because of the gravity of the hurts, the limitation of equipment, and precarious conditions of asepsis. They use external fixation as an initial treatment at the nearest health centre. And they delay the definitive treatment to be realized in better conditions. Our study aims to assess the outcome of damage control orthopaedic (DCO) strategy in military ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In addition, more type III fracture cases were found in the DC group and fracture type was also identified as a marginally significant influencer for treatment selection. This is in line with the above-mentioned study [ 17 ] and a previous retrospective study performed on military ballistic limb trauma in Tunisia, where they found that a type III of Gustilo skin opening was significantly associated with local complications [ 18 ]. Given that some inflammatory indices were shown to reach the maximum values at the time of admission before surgery, DC treatment prior to ICU admission may have a positive impact on infections.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, more type III fracture cases were found in the DC group and fracture type was also identified as a marginally significant influencer for treatment selection. This is in line with the above-mentioned study [ 17 ] and a previous retrospective study performed on military ballistic limb trauma in Tunisia, where they found that a type III of Gustilo skin opening was significantly associated with local complications [ 18 ]. Given that some inflammatory indices were shown to reach the maximum values at the time of admission before surgery, DC treatment prior to ICU admission may have a positive impact on infections.…”
Section: Discussionsupporting
confidence: 91%
“…In a prospective, randomized, multicenter study, sustained inflammatory response was only observed after primary intramedullary femoral instrumentation, but not after initial external fixation or after secondary conversion to an intramedullary implant [ 8 ]. In a retrospective study carried out on patients with gunshot limb trauma treated by DC surgery, DC was shown to be able to accelerate wound healing and protect against infection, which could shorten the delay of conversion from external fixation into an internal osteosynthesis [ 23 ]. In term of DC treatment for multiple trauma, it is suggested that DC can effectively reduce the mortality and complication rate, as well as shorten the ICU duration [ 24 ].…”
Section: Discussionmentioning
confidence: 99%